INDUSTRIALISED BUILDING SYSTEM (IBS) IN PUBLIC BUILDING CONSTRUCTION: PROFITABILITY ON THE IMPLEMENTATION IN SCHOOL BUILDING - Shafikah Saharuddin; Nazirul Syazani Shamsudin; Noor Anisah Abdullah@Dolah; Mohd Khairul Amri Ramly; Nur Fatiha Mohamed Yusof; Siti Nur Aishah Mohd Noor (Journal of Islamic, Social, Economics and Development, 2022)
Industrialized Building System (IBS) was introduced and developed in Malaysia to be part of the solution to address the increasing demand for affordable housing, providing answer on foreign labour problems, improving cost effectiveness, and ultimately refining the quality, efficiency, and productivity of the construction industry. This paper intended to identify and discover the profitability factors from IBS application among contractors. Quantitative method of questionnaires survey was distributed to various contractors in Selangor which have experienced IBS construction mainly on public building projects. Ideally, the researcher found that by reducing number of labour, enhancing the knowledge of IBS player, reducing construction period and reducing waste material on site area are among the factors that bring profitability upon using IBS method.